Gordon Parks papers - Parks, Gordon, 1912-2006.; Parks, Gordon, 1912-2006.; Parks, Gordon, 1912-2006.; Gordon Parks Archives in the Library of Congress
Correspondence, speeches, writings, film scripts, notes, project proposals, contracts, production material, financial records, and other papers documenting Parks's career as a writer, photographer, and producer and director of films. Includes drafts of The Learning Tree (1963) and Flavio (1978) as well as film scripts and production materials for The Learning Tree (1969) and Parks's ballet, Martin, about the life of Martin Luther King, Jr., filmed in 1989 for public television.
Library of Congress Music Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Photographer, author, filmmaker, and composer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: The Gordon Parks Archives in the Library of Congress.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968.; American literature; Ballet -- United States; Motion pictures, American; Photography -- United States; Authors; Composers; Motion picture directors; Photographers